Causal Power as a Structural Idea: A Comparative Study - Chen, Szu-Ting (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2011)
How do we typically construct a causal explanation of a target phenomenon? If we regard the phenomenon as a result of an interaction between two objects (or events), normally we would explain it by positing one of the objects (or events) as a factor that has the power to cause a change in the other object (or the other event) so that the change is regarded as the effect. This image of causal explanation is generally regarded as being Western in that it follows from Aristotle’s classical idea of causation which maintains that causation results in a change between material and form of entity in the world. In China, however, the classical idea of causation involves other elements of which individual entity is only one of the components. In addition to an entity’s power of causation and a resulting change in the material and form of the entity, Chinese thinkers suppose that, to make any explanation of a causal phenomenon, we must consider a number of essential components: other relevant entities in the world, their powers and their relations with the entity in question. These two traditions present different focal points in the idea of causation. But is there a chance that these two positions can be moderated so that we can develop a new position that includes the best parts of these two positions? In this paper, I first introduce Aristotle’s idea of causation and then describe the structural idea of causation proposed by Chinese thinkers. Then I describe a down-to-earth case of causal inquiry to show that contemporary Western philosophers of science, if we look from the perspectives of these two traditions, can provide a moderated account by combining the best parts of these traditions.